Advanced Desulfurization via Ultrasonic-Assisted Oxidative Methods in Gasoline and Crude Oil Towards Sustainability - Kate Andre T. Alviar; Angel Nicole V. Arbilo; Stephen S. Correa; Angelo Earvin Sy Choi (Chemical Engineering Transactions)
The presence of sulfur in crude oil and gasoline is crucial in both environmental and industrial contexts. This paper explores the intricate nature of sulfur, including elemental sulfur, hydrogen sulfide, carbonyl sulfide, and various organic compounds like thiophene derivatives. Effective sulfur management is essential due to its harmful effects on oil processing catalysts and the environment, leading to air pollution and acid rain. Reviewing environmental regulations mandating a minimal sulfur limit of 10 ppm in gasoline emphasizes the urgent need for enhanced desulfurization methods to address the adverse impacts of burning high-sulfur fuels on the environment and fuel efficiency. The review delves into Ultrasonic-Assisted Oxidative Desulfurization (UAOD), an innovative technique that maximizes sulfur removal from petroleum products. This process harnesses the power of ultrasonic waves to elevate heterogeneous reactions and optimize the effectiveness of oxidants, increasing the overall efficiency of sulfur removal. UAOD is a promising method for addressing sulfur-related challenges within the petroleum sector, as it yields enhanced desulfurization results and operational efficacy. Response Surface Methodology (RSM) efficiently optimizes parameters across various manufacturing procedures, including desulfurization studies, using designs like Box-Behnken or central composite. RSM effectively optimizes reactions affected by independent variables, demonstrated in the desulfurization of diesel and gasoline using methods like Mixing-assisted Oxidative Desulfurization (MAOD) and UAOD with NaPW/H2O2.